Organized Secularism in the United States New Directions in Research - Cragun, Ryan T. (De Gruyter, 2017)
Recent decades have witnessed the dramatic growth of an organized secularist movement that serves the needs of and advocates for the nonreligious. This volume brings together the latest research on organized secularism in the US, including its history, institution building, activist and political strategies, and its social functions in the lives of secularist individuals and families.